One-pot synthesis of biobased acrylic microcapsules for controlled release of fragrance in consumers products - Ng, Mandy (2024)
Microcapsules were synthesized using fully biobased monomers (itaconic acid (IA) and its derivatives) and partially biobased monomers (tetrahydrofurfuryl methacrylate and glycerol dimethacrylate) via one-pot interfacial radical polymerization for encapsulating fragrance oil. The loading capacity (the fraction of the fragrance oil in the entire mixture (slurry)) was as high as approximately 31 wt %, which is practically attractive. The three monomers were effectively polymerized at the oil-water interface to form a dense shell in the microcapsule, and hence, nearly all (100%) of the encapsulated fragrance oil was stably present in the microcapsule and did not diffuse out of the microcapsule even at an elevated temperature at 120 °C. The effects of the hydrophilicity of IA and its derivatives and the stirring speed during the polymerization were comprehensively studied. Hydrophilic itaconates tended to efficiently generate dense shells compared to hydrophobic itaconates, and there was an optimal stirring speed (900 rpm in this particular study). The polymerization behavior was also monitored in detail over the polymerization time. The obtained microcapsules were synthesized from biobased monomers and offer sustainable approaches for fragrance oil encapsulation. The obtained microcapsules were able to be deposited onto fabrics and also to rupture by mechanical force, demonstrating potential for laundry applications and fragrance release from the microcapsule by friction.